PENGEMBANGAN MEDIA INFOGRAFIS MATERI HIMPUNAN UNTUK MENINGKATKAN BERPIKIR KREATIF SISWA KELAS VII - Lina Ferdiana; Muhammad Baidawi; Fitria Khasanah; Abdul Hamid Bachtiar (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2024)
The low mathematical abilities of Indonesian students in the PISA 2022 study and limited creativity explain the concept behind this research. This problem is exacerbated by conditions at SMP IT Daar El-Qur'an, where teachers have not optimized digital media even though the majority of students are facilitated with Android devices. The focus of this research is to develop an infographic website media for collection material to improve the creative thinking of seventh-grade students. The research method applied is Research and Development (R&D) with the ADDIE model through five important stages: analysis, design, development, implementation, and evaluation. Quantitative data from the research results show the level of media validity from experts reached an average percentage of 85.18%, categorized as very valid. The practicality test by teachers and small groups of students obtained a score of 93.63%, categorized as very practical. Meanwhile, the media effectiveness test recorded a percentage of 61.68% in the effective category. The results of the measurement of students' creative thinking levels showed 2 students in the high category, 16 in the medium category, and 2 in the low category. The main conclusion of this development research confirms that the infographic website media for set material has been tested to be valid, practical, and effective, so it is very suitable and recommended for use in the mathematics learning process to spark students' creativity. ABSTRAK Rendahnya kemampuan matematika siswa Indonesia dalam studi PISA 2022 serta keterbatasan kreativitas menjelaskan konsep melatarbelakangi penelitian ini. Masalah tersebut diperkuat dengan kondisi di SMP IT Daar El-Qur'an, di mana guru belum mengoptimalkan media digital meski mayoritas siswa difasilitasi gawai android. Fokus penelitian ini adalah mengembangkan media website infografis materi himpunan untuk meningkatkan berpikir kreatif siswa kelas VII. Metode penelitian yang diterapkan adalah Research and Development (R&D) dengan model ADDIE melalui lima tahapan penting: analisis, desain, pengembangan, implementasi, dan evaluasi. Data kuantitatif hasil penelitian menunjukkan tingkat kevalidan media dari para ahli mencapai rata-rata persentase 85,18% dengan kategori sangat valid. Uji kepraktisan oleh guru dan siswa kelompok kecil memperoleh skor 93,63% sehingga dikategorikan sangat praktis. Sementara itu, uji keefektifan media mencatatkan persentase sebesar 61,68% dalam kategori efektif. Hasil pengukuran tingkat berpikir kreatif siswa menunjukkan 2 peserta didik berada pada kategori tinggi, 16 berkategori sedang, dan 2 berkategori rendah. Simpulan utama dari riset pengembangan ini menegaskan bahwa media website infografis materi himpunan teruji valid, praktis, serta efektif, sehingga sangat layak dan direkomendasikan untuk digunakan dalam proses pembelajaran matematika guna memantik daya kreativitas siswa.